Toward the Understanding of ‘The Human in Engineering: A Discourse Analysis - Pasmanik-Volochinsky, D; Castillo-Sepulveda, J (Taylor and Francis Ltd., 2021)
This study addresses the interpretations of the human in the discourse of civil industrial engineers in Chile and analyses their relationship with ethics and training. We argue that engineering is a heterogeneous activity that requires the alignment of multiple elements. Among these, assumptions about the human influence both the design of productive processes and the ways in which humans participate in organisations. Considering these aspects, we analysed the interpretative repertoires present in the discourse of civil industrial engineers, generated through individual and group interviews. We describe three ways in which the human is understood in engineering: in the casual, caring, and typification repertoires. After describing them in terms of how they discursively perform versions of the human, we discuss their ethical and practical implications for the engineer training processes. We conclude by discussing how viewing ethics as a product of daily practices can influence both training and daily professional activity. © 2021 SEFI.